Evaluation of Infection Control Methods Using by Hemodialysis Units' Staff - Aliasgharpoor M; Bassampoor SH; Bahrani N (Tehran University of Medical Sciences, 2007)
Background & Aim: Hemodialysis centers are highly susceptible to nasocomial infections due to application of hemodialysis machines, medical equipment, and invasive techniques and devices. This research was carried out in order to evaluate methods of infection control using by staff of hemodialysis centers.Methods & Materials: In this descriptive study, all hemodialysis units in hospitals of Tehran University of Medical Sciences (n=4) were studied. Data were gathered using a 3-section questionnaire as well as five series of check-lists that were designed to evaluate physical characteristics of the units, methods of disinfection processes of the units, hemodialysis machines, and common equipment, and finally precaution measurements using by the staff. Data were described using SPSS statistical software. Results: Research findings showed that just one of the study units was appropriate regarding physical characteristics of the units. Method of disinfection of hemodialysis centers was appropriate in 50 per cent of the study units and it was relatively appropriate in the rest. Disinfection of hemodialysis machines was appropriate in all units. Regarding disinfection of the shared equipment, all units were relatively appropriate. In 25 per cent of the units, staff had relatively appropriate precaution measurements and the rest (75 per cent) had inappropriate measurements.Conclusion: Results showed that the methods of infection control using by the staff of hemodialysis centers in hospitals of Tehran University of Medical Sciences were not appropriate.